(untitled) (Research, Society and Development, 2022)
The objective of the study was to evaluate and compare the floristic dynamics of two forest fragments constituted by Agroforestry Systems and capoeira as a way of recovering a degraded area. The study was conducted in an area of 125 ha that is located in the municipality of Igarapé-Açu/PA. For floristic and structural analysis of the two forest fragments, two censuses were carried out, the first in 2018 and the second in 2020. Phytosociological variables were calculated, such as: density, dominance, frequency and sociological position, relative and absolute values for the evaluation of the species expanded importance value index (IVIA), species coverage value index (IVC), Shannon-Weaver diversity index (H’), Simpson dominance index (C), Pielou equitability index (J’) and Jaccard similarity index, the mean annual periodic increase (IPMA) was necessary and the mortality rate of capoeira and Agroforestry Systems species. The two forest fragments diametric distribution in the form of an “inverted J”, the Shannon-Weaver index (H’) varied from 3.08 in 2018 to 3.03 in 2020 in capoeira and from 2.91 in 2018 to 2.83 in 2020 at Agroforestry Systems, in both treatments the index was considered low, showing a medium diversity, the most expressive species in capoeira were Myrcia sylvatica, Myrciaria tenella, Myrcia bracteata, Tapirira guianensis, Attalea maripa, no longer Agroforestry Systems were Jacaranda copaia, Acacia mangium, Lacistema pubescens, Myrcia sylvatica, Vismia guianensis. The mortality rate of capoeira was 10.7% higher compared to that of Agroforestry Systems. However, both treatments have a high coverage value index, which constitutes soil covered by biomass, plants mainly of the middle and upper strata and can correlate with superficial and deep roots, facilitating water infiltration and nutrient cycling and reducing erosion. therefore recovering a degraded area, nevertheless these two forest fragments are still far from reaching the recovery of biodiversity.